2020
DOI: 10.1111/apa.15682
|View full text |Cite
|
Sign up to set email alerts
|

Usability and acceptability of a multimodal respiratory rate and pulse oximeter device in case management of children with symptoms of pneumonia: A cross‐sectional study in Ethiopia

Abstract: Aim Pneumonia is the leading infectious cause of death among children under five globally. Many pneumonia deaths result from inappropriate treatment due to misdiagnosis of signs and symptoms. This study aims to identify whether health extension workers (HEWs) in Ethiopia, using an automated multimodal device (Masimo Rad‐G), adhere to required guidelines while assessing and classifying under five children with cough or difficulty breathing and to understand device acceptability. Methods A cross‐sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 24 publications
(47 reference statements)
3
25
0
Order By: Relevance
“…A previous hospital-based study in Ethiopia from the ARIDA group assessed the usability of the Masimo Rad G pulse oximeter and reported that children were feeding or drinking, or not calm before or during RR counting, in up to 15% RR measurements, which corresponds with our observations [14]. They also reported slow performance with a median time of almost 6 min necessary for automated RR counting [14]. Finally, they reported failure to count the RR with the automated method after three attempts in 8% of children [14].…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…A previous hospital-based study in Ethiopia from the ARIDA group assessed the usability of the Masimo Rad G pulse oximeter and reported that children were feeding or drinking, or not calm before or during RR counting, in up to 15% RR measurements, which corresponds with our observations [14]. They also reported slow performance with a median time of almost 6 min necessary for automated RR counting [14]. Finally, they reported failure to count the RR with the automated method after three attempts in 8% of children [14].…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies in children under five years old in low-resource settings also reported difficulties to perform RR counting according to the WHO guidelines and a suboptimal performance of Masimo Rad G pulse oximeter for automated RR counting. A previous hospital-based study in Ethiopia from the ARIDA group assessed the usability of the Masimo Rad G pulse oximeter and reported that children were feeding or drinking, or not calm before or during RR counting, in up to 15% RR measurements, which corresponds with our observations [14]. They also reported slow performance with a median time of almost 6 min necessary for automated RR counting [14].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations